2021
DOI: 10.1186/s12937-021-00733-1
|View full text |Cite
|
Sign up to set email alerts
|

Dietary macronutrient intake according to sex and trait anxiety level among non-diabetic adults: a cross-sectional study

Abstract: Background Studies suggest that anxiety is correlated with eating behavior, however, little is known about the association between anxiety status as predictor of dietary macronutrient intake. The aim of the present study was to investigate the sex-stratified cross-sectional associations of trait anxiety with intake of various macronutrients in a large population-based sample of non-diabetic adults. Methods N = 20,231 participants (mean age = 53.7 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…First, the cross-sectional design does not allow for causal or chronological inference. Prior research has shown that dietary intake and mental health status can mutually impact each other [ 14 , 15 , 58 , 59 ]. Future prospective research in this domain is needed to shed light not only on causality but also on the potential bidirectional association between macronutrient intake and comorbidity of anxiety and ED.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, the cross-sectional design does not allow for causal or chronological inference. Prior research has shown that dietary intake and mental health status can mutually impact each other [ 14 , 15 , 58 , 59 ]. Future prospective research in this domain is needed to shed light not only on causality but also on the potential bidirectional association between macronutrient intake and comorbidity of anxiety and ED.…”
Section: Discussionmentioning
confidence: 99%
“…The higher the score, the greater the proneness to anxiety. Considering the objectives of this study and for purposes of consistency with prior research [ 14 , 15 ], only the trait-anxiety subscale (STAI-T) was used for this analysis. It evaluates trait anxiety, characterized by a relatively stable tendency to exhibit tension and anxiety (i.e., state anxiety) in a variety of situations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher the score, the greater the proneness to anxiety 42 . Considering the objectives of this study and for purposes of consistency with prior research 10 , 11 , we used only the trait-anxiety subscale (STAI-T). It assesses anxiety proneness as a relatively stable personality feature 31 .…”
Section: Methodsmentioning
confidence: 99%
“…Regarding anxiety disorders, there is some, albeit inconsistent cross-sectional evidence of the link with overall and specific carbohydrate intake 9 11 , glycemic index/load 12 , insulin index 13 , soft drinks 14 , 15 , added sugars 16 , whole grains and fruit intake 17 24 . A scoping review of the relationship between diet and prevalence or severity of anxiety concluded that increased intake of sugar and refined carbohydrates was positively associated, while fruit intake was inversely associated with anxiety 25 .…”
Section: Introductionmentioning
confidence: 99%